Growing from the Inside Out : An Exploratory Investigation Into the Construct – Spirituality - Bantha, Tapas; Panda, Tapan Kumar; Sahni, Sanjeev P. (Prabandhan: Indian Journal of Management, 2021)
Our quest for understanding the universe and laws associated with it has driven civilization to a realization that laws of nature, the supreme, and growing from the inside out is the real education that one can have. Growing from inside out is the path of spirituality that each one pursues. This research paper made a humble attempt towards examining the nature and meaning of the notion ‘spirituality’ and individual metaphors people hold towards it across professions. We used qualitative data for exploring the concept of spirituality among the professionals from various professions. This exploratory study led to 15 propositions. The thematic map presented in this paper helped in developing propositions for studying the complex, abstract, and abstruse concept of spirituality.